One device does not fit all: limited results of using a Sort-X grid in the multi-species trawl fishery in the Gulf of Cádiz - Gamaza, MariÁngeles (2019)
A Sort-X grid device with four different bar-spacing grids (25, 30, 40 and 50 mm) was tested in the Gulf of Cádiz (GoC) on-board commercial trawlers. A total of 83 fish, five crustacean and nine cephalopods species were sampled in 282 hauls. Most of the target and commercial bycatch species were sorted out by the grid with the exception of hake. Merluccius merluccius (L.). Additionally, common pandora, Pagellus erythrinus (L.), sardine, Sardina pilchardus (Walbaum), octopus, Octopus vulgaris Lamark, and cuttlefish, Sepia officinalis L., also showed a sizeable retention for some of the grid bar spacing. Statistical modelling of selectivity at length for hake found influence of depth on the selection parameters. Lengths at 50% retention for hake were estimated to be 27.4, 30.3, 36.3 and 42.3 cm TL for 25–50 mm bar spacing, respectively, all above the minimum conservation reference size (MCRS) in the GoC. The probability of hake contacting the grid was estimated as 0.95. Overall, although the selective device showed a good performance for hake, it is not appropriate for improving the fishing pattern of a multi-species trawl fishery such as that of the GoC.